Crimean Tatars in Early 20-th Century Turkey (Through the Pages of the Newspaper “Istanbul News”) - M.G. Zulpukarova, Elmira (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to offer insight into the situation of the Crimean Tatars in Turkey relating to the emigration of a significant part of the Crimea’s Muslim population and their tragic fate abroad. Crimean Tatars, who had been the mainstay of the Crimean Khanate, were one of the largest ethnic groups that migrated to Turkey in the late 19th and early 20th centuries. Research interest in this topic is due to the discovery of an article, The Resettlement Issue in Turkey, published in the newspaper Stambulskiye novosti (Istanbul News), which came out for a short period of time in Constantinople in 1909-1910. Its only surviving copy has been preserved in the Archive of the Foreign Policy of the Russian Federation. The Russian-language weekly Istanbul News provided, above all, Russian readers and Russian émigrés who lived in Turkey in the early 20th century with the opportunity to stay informed of the events taking place in the Ottoman Empire. The events of those years are of special interest to present-day researchers and to a wide general readership. Materials in this paper are introduced for the first time into research literature, complementing the existing sources on the resettlement of the Crimean Tatars to Turkey in the beginning of the 20th century, their situation, and their tragic fate. Research work conducted on this source confirmed that the history of the Crimean Tatars had been overshadowed by tragic events resulting from the migration of a significant part of them to Turkey. The Crimean Tatars, who had left the Crimea and migrated to Turkey, endured considerable hardship. The existing publications on the situation of these émigrés in Turkey and their fate have not yet been sufficiently studied despite the significance and relevance of the topic. Importantly, the consequences of the Crimean Tatars’ migration to Turkey were truly disastrous. Settlers incurred a heavy loss of people. Mass migration and a high mortality rate during resettlement are a major tragedy in the history of the Crimean Tatars.